ESAP competencies for Malaysian engineering universities’ educators: a conceptual framework - Nor Yazi, Khamis; Supyan, Hussin; Nor Fariza, Mohd Nor (Global Illuminators, 2013)
This study proposes a conceptual framework in identifying specific competencies for English for Specific Academic Purposes (ESAP) ESL educators teaching at engineering universities. The increasing demand for effective language and communication skills in engineering fields has prompted the need of quality ESAP educators. However, few studies specify on finding the required competencies for the educators. Structured by three elements from the Malaysian Teacher Standards (2009) i.e. Values, Knowledge and Skills to define the competencies, the framework is supported by the ESP Learning Centred Approach (Hutchinson & Waters, 1987) and Critical EAP Theory (Benesch, 2001). Three international frameworks, the Professional Service Standards for ELT (Walker, 2011), BALEAP TEAP Competency Framework (BALEAP, 2008) and ESP/EAP characterisations (Hyland, 2007), were adapted in identifying the competency items for the educators. The study proposes mixed methods of Delphi and survey techniques. The proposal aims to elevate the educators’ quality teaching and professional standards.